2010
DOI: 10.1080/13670050903342019
|View full text |Cite
|
Sign up to set email alerts
|

What you hear and what you say: language performance in Spanish–English bilinguals

Abstract: Purpose-This study assesses the factors that contribute to Spanish and English language development in bilingual children. Method-757Hispanic Pre-kindergarten and kindergarten age children completed screening tests of semantic and morphosyntactic development in Spanish and English. Parents provided information about their occupation and education as well as their children's English and Spanish exposure. Data were analyzed using zero-inflated regression models (comprising a logistic regression component and a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
228
3
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 264 publications
(281 citation statements)
references
References 31 publications
34
228
3
4
Order By: Relevance
“…Results support findings that as a group, young HSs demonstrated higher grammatical accuracy in the home language, Spanish, while learners are early in the process of English second language acquisition [65,66]. However, our findings also indicate English grammatical development begins early, with kindergarteners demonstrating higher levels of emerging grammatical production in English as compared to Spanish.…”
Section: Discussionsupporting
confidence: 80%
“…Results support findings that as a group, young HSs demonstrated higher grammatical accuracy in the home language, Spanish, while learners are early in the process of English second language acquisition [65,66]. However, our findings also indicate English grammatical development begins early, with kindergarteners demonstrating higher levels of emerging grammatical production in English as compared to Spanish.…”
Section: Discussionsupporting
confidence: 80%
“…Because language proficiency and language ability are difficult to disambiguate in a sample of children with potential SLI, we determined language dominance on the basis of detailed parent and teacher interviews of children's language exposure and use (Gutierrez-Clellen & Kreiter, 2003). Language exposure, use, and history are highly related to children's language performance (Pearson, Fernández, Lewedeg, & Oller, 1997), but the nature of the relationship varies by domain (Bedore et al, 2012;Bohman et al, 2010). Thus, our approach enabled evaluation of language performance across children relative to their linguistic environment.…”
Section: The Longitudinal Portion Of the Studymentioning
confidence: 99%
“…More information about the children's language skills and performance on the screener is provided by Bohman, Bedore, Peña, Mendez-Perez, and Gillam (2010) and Peña et al (2011).…”
Section: Recruitment and Screeningmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have found measures of bilingual children's language use were related to children's language skill and have suggested that using a language plays a role in acquiring that language (Bedore, Peña, Summers, Boerger, Resendiz, Greene, et al, 2012;Bohman, Bedore, Peña, Mendez-Perez, & Gillam, 2010). Language use, or output, has not received much attention in the first language acquisition, but in the field of second language acquisition the Output Hypothesis has been proposed to explain why immersion students, who experience a great deal of high quality input, nonetheless fail to achieve high levels of proficiency in their second language (de Bot, 1996;Swain, 2005).…”
Section: Effects Of Outputmentioning
confidence: 99%